Democracy and its foundations in Norberto Bobbio. [Portuguese] (2010)
One of the central themes of political philosophy is Bobbian democracy. In consequence there are many approaches to the philosopher Turin along its vast bibliography. In this article it would not be possible to make more than a brief tour on this extensive topic which deals with Bobbio. Our proposal is the focus on some of the aspects that can bring us closer to the nucleus of Bobbian thought about democracy and its vicissitudes, which itself would justify an completely autonomous line of investigation. In these lines I shall do more exact those dimensions which deal with the concept of democracy in Bobbio. Then, the objective is linking this concept with the sense and importance enjoyed in the concept of political participation in the context of his political work, in which the concept of activae civitatis is of an outstanding position.